Assessing associations of clinical factors and feeding practices with infantile urolithiasis: Insights from a nationwide study - Doven, Serra Surmeli; Genc, Esra; Gencler, Aylin; Simsek, Ozgur Ozdemir; Tunc, Ali; Mutlubas, Fatma; Alpay, Harika (Elsevier Sci Ltd, 2026)
Introduction The incidence of infantile urolithiasis (IU) has been rising, attributed to factors such as climate change, the widespread use of ultrasonography, dehydration, and alterations in nutritional practices. Studies investigating the influence of infant feeding practices on stone formation remain limited. Objectives This study aims to identify the risk factors associated with stone formation in infants and to evaluate whether formula feeding influence the development of IU. Study design Infants aged 1-12 months who were diagnosed with IU and followed up at pediatric nephrology clinics in 19 centers across Turkiye between January 2022 and January 2024 were included in the patient group. Healthy infants served as the control group. A structured questionnaire assessing nutritional, demographic, and clinical characteristics was administered to both groups. A comparative analysis was conducted between the patient and control groups. Results Among the 1.094 infants included in the study, 45.7 % (n = 500) comprised the patient group, while 54.3 % (n = 594) were in the control group. A history of urinary tract infection, family history of urolithiasis and stone surgery, and vitamin D supplementation were significantly more common in the patient group compared to the control group (p = 0.006, <0.001, <0.001, and <0.001, respectively). Urine densities ranging from 1010 to 1020, as well as those greater than 1020, were more frequently observed in the patient group than in the control group (30.3 % vs. 20.1 % and 5.9 % vs. 0.4 %, respectively. Exclusively formula feeding (OR = 1.96 [1.094-3.521], p = 0.024), vitamin D consumption (OR = 3.994 [2.348-6.793], p < 0.001), and a family history of stone surgery (OR = 2.423 [1.457-4.027], p = 0.001), were identified as independent risk factors for stone formation. Discussion Turkiye is an endemic region for urolithiasis due to factors such as a high animal-based diet and a hot climate. Urolithiasis is reported to affect 10-20 % of children, with infantile urolithiasis accounting for 9-23 % of this incidence. This study represents the largest case series on infantile urolithiasis, investigating the impact of nutrition on its development. Conclusions Exclusive breastfeeding should be encouraged, as it serves as a protective factor against stone formation in infants. Preventing dehydration is also essential. Infants receiving vitamin D supplementation, as well as those with a family history of urolithiasis or stone surgery, should be closely monitored for the potential development of urinary stones.
Keywords: Infancy; Urolithiasis; Breast-feeding; Renal stone; Nutrition